2019
DOI: 10.1109/jstqe.2018.2833205
|View full text |Cite
|
Sign up to set email alerts
|

MAESTROS: A Multiwavelength Time-Domain NIRS System to Monitor Changes in Oxygenation and Oxidation State of Cytochrome-C-Oxidase

Abstract: We present a multiwavelength, multichannel, time-domain near-infrared spectroscopy system named MAESTROS. This instrument can measure absorption and scattering coefficients and can quantify the concentrations of oxy- and deoxy-haemoglobin ([HbO2], [HHb]), and oxidation state of cytochrome-c-oxidase ([oxCCO]). This system is composed of a supercontinuum laser source coupled with two acousto-optic tuneable filters. The light is collected by four photomultipliers tubes, connected to a router to redirect the signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(67 citation statements)
references
References 69 publications
2
65
0
Order By: Relevance
“…However, TD systems are more expensive than CW instruments and, to date the majority of them are prototypes developed in laboratories and not commercially available; (3) Broadband NIRS instruments that use hundreds of NIR wavelengths to measure changes in brain tissue cortical metabolism by quantification of the changes in the oxidation state of cytochrome C oxidase (or oxCCO). Most of these devices are CW based, but recently TD broadband instrumentation has also been developed . As before, prototype systems are currently used in some laboratories but they are not commercially available.…”
Section: History and Basics Of Near‐infrared (Nir) Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…However, TD systems are more expensive than CW instruments and, to date the majority of them are prototypes developed in laboratories and not commercially available; (3) Broadband NIRS instruments that use hundreds of NIR wavelengths to measure changes in brain tissue cortical metabolism by quantification of the changes in the oxidation state of cytochrome C oxidase (or oxCCO). Most of these devices are CW based, but recently TD broadband instrumentation has also been developed . As before, prototype systems are currently used in some laboratories but they are not commercially available.…”
Section: History and Basics Of Near‐infrared (Nir) Spectroscopymentioning
confidence: 99%
“…Most of these devices are CW based, 89 but recently TD broadband instrumentation has also been developed. 90 As before, prototype systems are currently used in some laboratories but they are not commercially available.…”
Section: Future Directions In Fnirs Hardware Developmentmentioning
confidence: 99%
“…The new hyperspectral illumination and detection approach, as well as the hyperspectral processing algorithms here reported, can be implemented in a benchtop HSI system and validated under controlled experimental conditions, e.g., using blood and yeast liquid phantoms. 39 Moreover, the tested HSI configuration could be further explored and developed in the future, e.g., by spatially scanning larger FOVs including both vasculature and gray matter or by applying modulated illumination techniques similar to those used in spatial frequency-domain imaging and structured illumination imaging. 40,41 The findings of the four studies reported here can be translated into an experimental setting and could improve the performances of any benchtop NIR HSI system that targets the relative changes of concentration of HbO 2 , HHb, and oxCCO on the exposed cortex, whereas the MC framework can be easily coupled with the instrumentation to aid hyperspectral data acquisition and reconstruction for in vivo applications.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike few wavelength time domain systems, broadband TD-DOS has the unique advantage of resolving an extended spectral range along with inherent benefits of depth segmentation using time gating and uncoupling of absorption from scattering. It is thus an ideal tool for exploration studies, where the key features of the tissue under study are understood, and the results, in turn, are exploited to create few wavelengths (typically smaller, cheaper, and simpler) dedicated systems [27,[36][37][38][39]. With the advent of new technologies, the complexity of time domain instruments has been reduced from laboratory to compact devices, portable on wheels [23,27,36,40].…”
Section: Introductionmentioning
confidence: 99%